2007
DOI: 10.1097/bot.0b013e318059aea3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of a Stability-Based Ankle Fracture Classification System

Abstract: The results support the hypothesis that a stability-based ankle fracture classification system can be prognostic. For unstable ankle fractures, the radiographic outcomes were better after surgery, when the decision for surgery was made on the basis of stability (P = 0.0173). Overall, non-operative treatment results were also better with stability-based treatment (P = 0.0299).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
82
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 56 publications
0
82
1
1
Order By: Relevance
“…It has been shown that stable ankle fractures can be treated conservatively with excellent results (Yde and Kristensen 1980, Ryd and Bengtsson 1992, Bauer et al 1985, Kristensen and Hansen 1985, Bauer et al 1987, Michelson 1995, Michelson et al 2007, van den Bekerom et al 2009, Pakarinen 2012, and recently a classification system based on ankle fracture stability was reported (Michelson et al 2007). The authors Review of the literature noted that a stability based classification system could be prognostic as well as guide in decision-making (Michelson et al 2007). These findings were further emphasized in a recent doctoral thesis (Pakarinen 2012).…”
Section: Classification Of Ankle Fracturesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that stable ankle fractures can be treated conservatively with excellent results (Yde and Kristensen 1980, Ryd and Bengtsson 1992, Bauer et al 1985, Kristensen and Hansen 1985, Bauer et al 1987, Michelson 1995, Michelson et al 2007, van den Bekerom et al 2009, Pakarinen 2012, and recently a classification system based on ankle fracture stability was reported (Michelson et al 2007). The authors Review of the literature noted that a stability based classification system could be prognostic as well as guide in decision-making (Michelson et al 2007). These findings were further emphasized in a recent doctoral thesis (Pakarinen 2012).…”
Section: Classification Of Ankle Fracturesmentioning
confidence: 99%
“…Unimalleolar fractures are usually stable, and can often be treated nonoperatively (Pakarinen et al 2011a, Pakarinen 2012). However, bi-and trimalleolar fractures are unstable injuries, and are normally treated by operative means (Michelson et al 2007, Pakarinen 2012 (Figure 1). …”
Section: Classification Of Ankle Fracturesmentioning
confidence: 99%
“…However, the results were far from satisfactory, and starting from the 1970's, the greatest emphasis was put on the anatomic reduction and rigid fixation of the lateral malleolus (DeSouza et al 1985). Year 2014, operative treatment of ankle fractures is based on the stability of the ankle joint (Michelson et al 2007, Gougoulias et al 2010, Pakarinen et al 2011a, Pakarinen 2012.…”
Section: Operative Treatment Of Ankle Fracturesmentioning
confidence: 99%
“…there is general consensus that the stability of the ankle mortise is the most important factor when choosing between operative and nonoperative treatment (Yde and Kristensen 1980a, Yde and Kristensen 1980b, bauer et al 1985b, Kristensen and hansen 1985, phillips et al 1985, Michelson 1995, Michelson 2007. bi-and trimalleolar fractures are considered unstable injuries and should be treated operatively (Yde and Kristensen 1980b, phillips et al 1985, ali et al 1987, Michelson 1995, Michelson et al 2007); however, in lateral malleolus fractures the ankle joint can be stable or unstable, depending on the mechanismIntroduction ideally, a classification system would help physicians determine the appropriate treatment method (Michelson et al 2007), but neither of the two most widely used classification systems for ankle fractures, the Lauge-hansen (Lauge-hansen 1950) and Weber (Muller et al 1979) systems, predicts fracture instability, and the values of these systems in choosing a treatment method are limited (Lindsjo 1985a, bauer et al 1987b, nielsen et al 1990, broos and bisschop 1991, rasmussen et al 1993, Michelson et al 1997, Gardner et al 2006c, haraguchi and armiger 2009. since the stability of the fractured ankle is the most important factor in choosing between operative and non-operative treatment, Michelson et al proposed a stability-based ankle fracture classification system that more clearly addressed this aspect (Michelson et al 2007).…”
Section: Exploration and Repair Of The Aitfl Is Not Needed In These Fmentioning
confidence: 99%
“…bi-and trimalleolar fractures are considered unstable injuries and should be treated operatively (Yde and Kristensen 1980b, phillips et al 1985, ali et al 1987, Michelson 1995, Michelson et al 2007); however, in lateral malleolus fractures the ankle joint can be stable or unstable, depending on the mechanismIntroduction ideally, a classification system would help physicians determine the appropriate treatment method (Michelson et al 2007), but neither of the two most widely used classification systems for ankle fractures, the Lauge-hansen (Lauge-hansen 1950) and Weber (Muller et al 1979) systems, predicts fracture instability, and the values of these systems in choosing a treatment method are limited (Lindsjo 1985a, bauer et al 1987b, nielsen et al 1990, broos and bisschop 1991, rasmussen et al 1993, Michelson et al 1997, Gardner et al 2006c, haraguchi and armiger 2009. since the stability of the fractured ankle is the most important factor in choosing between operative and non-operative treatment, Michelson et al proposed a stability-based ankle fracture classification system that more clearly addressed this aspect (Michelson et al 2007). operative treatment is indicated only for fractures in which the talus can move pathologically from the ankle mortise, which is the case in all bi-and trimalleolar fractures and lateral malleolar fractures with positive stress tests, and thus instability of the ankle mortise (Michelson et al 2007) (figure 1).…”
Section: Exploration and Repair Of The Aitfl Is Not Needed In These Fmentioning
confidence: 99%